The alignment of the knee joint in relationship to age and osteoarthritis: The Copenhagen Osteoarthritis Study - Laxafoss, Erling; Jacobsen, Steffen; Gosvig, Kasper K.; Sonne-Holm, Stig (Skeletal radiology, 2013)
Introduction The aim of the present study was to describe the changes in the axis of the knee joint in both radiologically osteoarthritic and non-osteoarthritic knees, on the basis of angles measurable in standardized clinical short knee radiographs, in a cross sectional study of an epidemiological cohort. Design From the third inclusion of the Copenhagen City Heart Study, 4,151 subjects were selected for standardized radiography of the knees. After censuring the inclusion, the resulting cohort was comprised of 3,488 individuals. Images were analyzed for radiological knee joint osteoarthritis (OA) and the anatomical femorotibial axis of the knee joint was measured. Results The prevalence of knee joint OA in males was 27.9 % and 27.5 %, for the left and right knees respectively. In females this was 32.8 % and 36.4 %. The mean knee joint angles were 4.11° in males; and 5.45° in females. A difference of 1.3° was found between the genders. In non-osteoarthritic knees the increase in valgus orientation in relationship to increasing age was found to be 0.03° and 0.04° per year, respectively, for males and females. Likewise, Kellgren and Lawrence found that OA was seen to influence a shift towards varus of 0.55°–0.76° per level of OA. Conclusion Stratification in accordance with morphological severity of OA documented a clear tendency for the axis of the diseased knees to depart from the mean, primarily in the direction of varus. In knees exhibiting no signs of radiographic osteoarthritis we found a significant relationship between increasing age and a shift in the anatomical axis in the direction of valgus.